Phytocompounds targeting epigenetic modulations: an assessment in cancer - Khan, Aqsa; Khan, Asifa; Khan, Mohammad Aasif; Malik, Zoya; Massey, Sheersh; Parveen, Rabea; Mustafa, Saad; Shamsi, Anas; Husain, Syed A. (Frontiers in Pharmacology, 2024)
For centuries, plants have been serving as sources of potential therapeutic agents. In recent years, there has been a growing interest in investigating the effects of plant-derived compounds on epigenetic processes, a novel and captivating frontier in the field of epigenetics research. Epigenetic changes encompass modifications to DNA, histones, and microRNAs that can influence gene expression. Aberrant epigenetic changes can perturb key cellular processes, including cell cycle control, intercellular communication, DNA repair, inflammation, stress response, and apoptosis. Such disruptions can contribute to cancer development by altering the expression of genes involved in tumorigenesis. However, these modifications are reversible, offering a unique avenue for therapeutic intervention.Plant secondary compounds, including terpenes, phenolics, terpenoids, and sulfur-containing compound are widely found in grains, vegetables, spices, fruits, and medicinal plants. Numerous plant-derived compounds have demonstrated the potential to target these abnormal epigenetic modifications, including apigenin (histone acetylation), berberine (DNA methylation), curcumin (histone acetylation and epi-miRs), genistein (histone acetylation and DNA methylation), lycopene (epi-miRs), quercetin (DNA methylation and epi-miRs), etc. This comprehensive review highlights these abnormal epigenetic alterations and discusses the promising efficacy of plant-derived compounds in mitigating these deleterious epigenetic signatures in human cancer. Furthermore, it addresses ongoing clinical investigations to evaluate the therapeutic potential of these phytocompounds in cancer treatment, along with their limitations and challenges.